Forest structure determines nest box use by Central European boreal owls - Ševčík, Richard; Kloubec, Bohuslav; Riegert, Jan; Šindelář, Jiří; Kouba, Marek; Zárybnická, Markéta (Scientific reports, 2022)
Nest boxes represent a popular tool to support secondary cavity-nesting species. Surprisingly, the benefits and limitations of nest boxes for target species in different environments are poorly understood. We performed a 3-years experimental study in two different Central European forests to evaluate nest box use and breeding performance of boreal owl ( Aegolius funereus ) — a species well known for its readiness to occupy nest boxes. Based on territorial vocalisation, two boreal owl populations 200 km apart were similarly abundant in their environments. However, only the boreal owl population in young restored Norway ( Picea abies ) and blue ( Picea pungens ) spruce-dominated forests on mountain plateaus readily occupied nest boxes with the occupancy reaching 8–15%. Nest boxes lost their supporting function for the boreal owl in mature Scots pine ( Pinus sylvestris )-dominated forests in the lowland, where the nest box occupancy reached 0–1%. As a result, the population of boreal owls that used nest boxes in the young restored forests produced 10 times more fledglings than the population inhabiting mature Scots pine forests. We explain the differences by the contrasting availability of natural tree cavities between the two study areas being much higher in mature Scots pine forests. For the first time, this study documents differences in nest box use despite similar food availability and population size of the target species. The study provides the findings-related recommendations for deploying nest boxes for boreal owls and points out a general lack of practical guides.